A Bibliometric Review of Volatility Spillovers in Financial Markets: Knowledge Bases and Research Fronts. Issue 5 (9th April 2021) - Chen, Jun; Yang, Lingling
ABSTRACT: This paper uses the bibliometric method of knowledge mapping analysis to clearly present the knowledge base and research fronts of cross-market volatility spillovers. The results provide strong evidence that, first, the general theme of volatility spillovers can be divided into a variety of research topics, four of which are on the dynamics of volatility spillovers in world financial markets of various types based on multivariate GARCH or VAR models and construct a crucial knowledge base for this field; second, three research fronts can be identified using burst analysis, and they focus on examining spillover directions and magnitudes, testing volatility spillovers related to oil markets and international risk transmission mechanism of emerging markets; and, third, the major contributing scholars come from institutions in the United States, China and European economies. Our conclusions offer some recommendations for market practitioners in their risk management and policy-making.